GAYA KOMUNIKASI SANTAI DAN AUTENTIK DALAM KONTEN PODCAST PODHUB SERTA IMPLIKASINYA TERHADAP DAYA TARIK DAN LOYALITAS AUDIENS GENERASI Z - Diva Almaidah S; Muh. Nabil Nabiyullah; Qudratullah (Hujjah: Jurnal Ilmiah Komunikasi dan Penyiaran Islam, 2026)
This study aims to analyze the casual and authentic communication style in podcast content on PODHUB and its implications for the attractiveness and loyalty of Generation Z audiences. This research employs a qualitative approach with a field research design. Data were collected through in-depth interviews, content observation, and documentation. The informants consisted of Generation Z audiences who actively consume PODHUB podcast content. Data analysis was conducted through data reduction, data display, and conclusion drawing. The results indicate that a casual communication style characterized by informal language, spontaneity, and flexible conversation enhances content attractiveness. Meanwhile, authenticity reflected through honesty, openness, and natural emotional expression plays a significant role in building trust and emotional closeness between hosts and audiences. This communication style not only increases audience engagement but also fosters long-term audience loyalty among Generation Z. The study concludes that casual and authentic communication styles are crucial factors in the success of podcast content in the digital era, particularly in attracting and retaining audiences.